Fat Mass Index and dietary behaviours of the Polish Border Guard officers - Anna Anyżewska (Roczniki Panstwowego Zakladu Higieny, 2019)
Background. Due to specific requirements of service, Border Guard officers should be characterized by good health. Whereas there is lack of studies assessing nutritional status as well as dietary behaviours among Polish Border Guard officers. Objective. The aim of the study was to assess the impact of dietary behaviours of the Polish Border Guard officers on the Fat Mass Index. Material and methods. The study was carried out with participation of 250 Border Guard officers (187 men and 63 women), aged 37±6; years of service: 12±6. Nutritional status was determined with the electrical bioimpedance method using the TANITA MC-780 analyzer. According to the calculated Fat Mass Index value each person was qualified to one of the following groups: fat deficit, normal fat or excess fat. The Border Guard officers were asked to fill in the original questionnaire containing questions about nutritional behaviours in line with the recommendations of the Swiss Food Pyramid for Athletes in the basic version. Results. The excessive amount of fat in every third officer of the Border Guard and numerous irregularities in eating behaviours were found. According to the food pyramid the smallest scale of rational dietary choices (especially regularity of meals, fruit and vegetable consumption) was characteristic of officers with excess fat. In addition, officers from the excess fat group obtained, on average, a lower sum of points for compliance of nutritional behaviours with the recommendations of the Swiss Food Pyramid than those from other groups (49% vs. 59% and 56%, p=0.002). Conclusions. There is a need for nutritional education and further monitoring of both the nutritional status and dietary behaviours of Border Guard officers.